Encountering habitus: The process of social change through social entrepreneurship - Bhatt, B. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
The purpose of this research is to investigate the potential of social enterprises in bringing social change through increasing participation of the most marginalized in social and economic activities. Specifically, the paper explores how the actions and practices of social enterprises can bring about social change in communities. Popularly known as change agents, social enterprises are expected to play an important role in addressing complex social challenges and transforming the social structure. However, critics have argued that the market-based solutions offered by social enterprises are limited in challenging ethical inertia that reflects internalized rules and moral dispositions resulting from habitus. Using an exemplary case of social enterprise in India, the paper argues that a focus on creating economic opportunities is limited and social enterprises need to incorporate the actions of recognition, reposition and representation to bring about change in communities. The findings of this paper have policy and research implications.
Keywords: Social Entrepreneurship, social change, ethical inertia, structural injustice, dynamic habitus, case study, India